The Eco-Phonetics Of Climate Displacement: Acoustic Differences In Speech Of Internally Displaced Students (IDPs) In Iraq - Omar Abbas Naithel; Ali Salah Salman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Displacement caused by climate is one of the most burning humanitarian matters of the twenty-first century, as millions of people of different nationalities of the world suffered this problem, and their linguistic environments also changed fundamentally. This project is based on the auditory differences of the speech pattern of the internally displaced students (IDPs) in Iraq and how environmental displacement and other climate-specific stressors can impact phonetic production. This study employs both a mixed-methods approach which incorporates both acoustic phonetics analysis and sociolinguistic interviews to analyze samples of speech among 120 IDP students between the ages of 14-22 in three camps in Kurdistan Region of Iraq. According to the findings, the displaced populations show considerable differences in the frequencies of the vowel formants, consonant rates of the articulations, and the prosodic patterns. The statistical tests prove that the displacement term, the exposure to various languages in camp conditions, and climate-related trauma will exhibit significant changes in phonetics being measurable. The study is an addition to the new branch of research in eco-phonetics as it draws an empirical relationship between environmental displacement and variation in speech and gives implications to educational intercession and linguistic integration programmes to the displaced groups.